PROFILE DERMATOGLIPHY OF PROFESSIONAL PADDLE PLAYERS OF BRAZIL (Fiep Bulletin - online, 2017)
The paddle is a strong sport in the brazilian southern region, but little publicized in the media and low in scientificpublications. It has similar features to tennis and squash. The dermatogliphy is a protocol to better assembly of the trainingprogram cycles, and look for possible talents. The study aims to determine which is the dermatogliphy profile of professionalpaddle players, comparing the results with other studies using the dermatogliphy as data collection method. They were selectedvoluntarily 20 professional male paddle players (age= 28,85 ± 6,18; stature (m) = 1,80 ± 0,05; body mass (kg) = 80,44 ± 8,25),who were competing in the 2nd stage of the Brazilians Championship of Paddle, held in Curitiba, PR, using the protocols ofCummins and Midlo (1961), stature and body mass (FERNANDES FILHO, 2003). For statistical analysis was the Shapiro-Wilktest used to check normality of variables and Pearson's correlation to check relationship between two parametric variables. Thedermatogliphy profile verified by fingerprints were: A= 0,65 ± 0,88; L= 6,4 ± 1,88; W= 2,95 ± 1,9; D10 = 12,30 ± 2,3; SQTL = 118,13± 23,42, with correlation between SQTL and D10 r = 0,64. Greater genetic predisposition was verified for explosive strength andspeed, and lower in coordination. It is recommended to apply more research in the form, relating dermatogliphy with othervariables within the sport, for further enrichment of information.